A systematic review of the effect of sleep interventions on presenteeism - Yuta Takano (BMC, 2021)
Abstract Background Sleep problems interfere with work performance. Decreased work productivity due to health problems is defined as presenteeism. Although empirical data on the improvement of presenteeism by sleep interventions have been published, a systematic review elucidating whether there is a difference in the improvement of presenteeism across various types of sleep interventions has not yet been published. This systematic review of studies aimed to clarify which sleep interventions are more likely to be effective in improving presenteeism. Methods The electronic databases PubMed, PsycINFO, and MEDLINE were used to perform a literature search (the start and end search dates were October 20, 2019, and March 11, 2020, respectively). A combination of terms such as “employee*,” “sleep,” “insomnia,” and “presenteeism” was used for the search. Both randomized and non-randomized control trials were included in this systematic review. Results Six types of sleep interventions were identified, including cognitive behavioral therapy for insomnia (CBT-I), sleep hygiene education, yoga, mindfulness, weight loss program, and changing the color temperature of fluorescent lights in the workplace. Only CBT-I improved both sleep problems and presenteeism compared with a control group. The results of this review also show that there is heterogeneity in the measurement of presenteeism. Conclusions The results of this systematic review suggested that CBT-I could be adapted for workers with sleep problems and presenteeism. We discussed whether CBT-I improved both sleep problems and presenteeism compared with other interventions. In addition, methods for measuring presenteeism in future research are proposed.